Karakteristik Sifat Fisis Tanah Lempung dengan Penambahan Serbuk Limbah Kulit Jagung - Muhammad Haviz Abdul Rohman; Athaya Zhafirah (Institut Teknologi Garut, 2026)
This study aims to determine the effect of adding corn husk waste powder on the physical properties of clay soil, which is known to have fine-grained characteristics and a high level of plasticity. The research was conducted experimentally in a laboratory by mixing corn husk powder waste into clay soil in three composition variations, namely 5%, 10%, and 15% of the soil’s dry weight. The physical properties of the soil examined included water content, unit weight, specific gravity, grain size distribution (sieve analysis), and soil consistency parameters such as liquid limit, plastic limit, and shrinkage limit. The results show that the addition of corn husk waste powder causes significant changes in most of the soil’s physical properties. Decreases were observed in water content, fine-grained fraction, liquid limit, shrinkage limit, and plasticity index. Meanwhile, increases occurred in unit weight, specific gravity, plastic limit, and the proportion of coarse grains. The mixture with a 15% composition produced the most substantial changes compared to the other compositions, indicating that an increase in corn husk content in clay soil is directly proportional to the magnitude of the changes. The contribution of this study lies in the utilization of agricultural waste, specifically corn husks, as an alternative material to improve the physical properties of clay soil. The results demonstrate potential applications in the field of geotechnical engineering, particularly for soil stabilization purposes, while also supporting a sustainable approach to organic waste management.